(untitled) (Research, Society and Development, 2020)
Due to the growth of tilapia production and adaptability to different breeding conditions, to advances in technology and its acceptability by the consumer, this can be a viable alternative for small and medium-sized rural producers to increase income and diversify production. This work aimed to estimate the production potential of Nile tilapia, in ground-excavated ponds, through spatial analysis using Geographic Information System (GIS). Three municipalities located in the center-south region of the state of Paraná, Brazil, were chosen, which are not considered producers of tilapia. Satellite images were used through the QGIS software to map the ground-excavated ponds, which made it possible to estimate the productive potential of the fish, taking into account in the calculation an average productivity of 54 t/ha/year. Finally, the ellipse technique of directional distribution was used in order to identify the behavior of the spatial distribution of the ponds, providing the knowledge in its density and orientation. The results showed that to obtain the best tilapia production it is necessary to work with a safe margin of approximately 300 days to fatten the fish, precisely because it respects the regional climate throughout the year and especially in the winter months, where there is less weight increase in the species. Also, it was estimated that there is the possibility that the region will slaughter 34.12 t/fish/day, under standardized conditions which is considered a relevant production, in relation to the national production data presented in recent years by official agencies.